BIOGEOGRAPHY OF THE NORTHERN PERI-TETHYS FROM THE LATE EOCENE TO THE EARLY MIOCENE. PART 3. LATE OLIGOCENE-EARLY MIOCENE. MARINE BASINS - Popov S.V.; Bugrova E.M.; Amitrov O.V.; Andreyeva-Grigorovich A.S.; Akhmetiev M.A.; Zaporozhets N.I.; Nikolaeva I.A.; Sychevskaja E.K.; Shcherba I.G. (My University, 2004)
This contribution, the third part of a monographic series, deals with the biogeography of the Tethys and Paratethys sea basins in the Late Oligocene and Early Miocene and includes reviews of the stratigraphy and paleogeography of the Paratethys, descriptions of the biogeographic distribution of planktonic foraminifers, nanno- and organic-walled phytoplankton, benthos (benthic foraminifers, ostracodes, and mollusks), and the ichthyofauna, and provides biogeographic zonation based on these groups. The final section deals with the evolution of the main biochores in the western Eurasian basins during the second half of the Paleogene and Miocene.
Keywords: Tethys; Paratethys; foraminifers; Cenozoic::Neogene::Miocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Eocene